1999
DOI: 10.1097/00007632-199911150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Unstable Thoracolumbar and Lumbar Spine Injuries Using Cotrel–Dubousset Instrumentation

Abstract: Cotrel-Dubousset instrumentation provided spinal stability in unstable injuries, forming a rigid construct and restoring physiologic thoracolumbar and lumbar postural contours because of its highly corrective effect in the sagittal profile with no loss of correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 20 publications
2
34
0
4
Order By: Relevance
“…[5] Torakolomber patlama kırıklarının tedavisinde, nö-rolojik arazı olan olgularda büyük oranda fikir birliği oluşmuş gibi görünse de, nörolojik arazı olmayan hastalarda konservatif ve cerrahi uygulamaların seçimi konusunda tartışmalar halen devam etmektedir. Bazı otörler cerrahi tedaviyle omurganın stabilizasyonunu ve spinal kanalın restorasyonunu savunurken, [7,24] bazı yazarlar ise cerrahi dışı tedaviyi savunmaktadır-lar. [2,3,32] De Klerk ve arkadaşları, konservatif tedaviyle kanal içi düzelmenin elde edildiğini ve hiçbir hastada takip sonunda nörolojik araz oluşmadığını bildirmiş-lerdir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…[5] Torakolomber patlama kırıklarının tedavisinde, nö-rolojik arazı olan olgularda büyük oranda fikir birliği oluşmuş gibi görünse de, nörolojik arazı olmayan hastalarda konservatif ve cerrahi uygulamaların seçimi konusunda tartışmalar halen devam etmektedir. Bazı otörler cerrahi tedaviyle omurganın stabilizasyonunu ve spinal kanalın restorasyonunu savunurken, [7,24] bazı yazarlar ise cerrahi dışı tedaviyi savunmaktadır-lar. [2,3,32] De Klerk ve arkadaşları, konservatif tedaviyle kanal içi düzelmenin elde edildiğini ve hiçbir hastada takip sonunda nörolojik araz oluşmadığını bildirmiş-lerdir.…”
Section: Discussionunclassified
“…Bu çalışmalarda kanal içi düzelme, çalışmaların bir parçası olarak bahsedilmiş ve homojen bir sınıflama ve tedavi yöntemi olarak bir karşılaştırma yapılma-mıştır ( Tablo 5). [1,3,[12][13][14]16,[21][22][23][24][25][26][27]39,[41][42][43] Bu çalışmada ise, uzun segment posterior enstrümantasyon ve kısa seviye füzyon uygulanan hasta grubunda daha anlamlı kanal içi düzelme elde edildi. Uzun segment enstrüman-tasyonda kırık omurganın iki seviye üstü ve iki seviye altında olmak üzere toplam dört omurgaya vida yerleştirilip rod üzerinden distraksiyon uygulandı.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…There is no consensus regarding optimal treatment and various conservative and operative options have been described in the literature with different inclusion criteria, follow-ups and evaluation tools. [14][15][16][17][18][19][20][21][22] There are no prospective randomised or controlled studies. A surgical fixation procedure for an unstable upper or middle thoracic fracture should be safe, correct the frequent kyphotic deformity and anterolisthesis and thereby decompress the spinal cord and maintain the deformity correction long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Gurr et al 50 found that two levels above and below the injured level in an unstable calf spine model provided more stiffness than the intact spine. Katonis et al 51 found that two levels above and one level below the fracture at the thoracolumbar junction and SSPF in the lumbar area provided stability and formed a rigid construct with no correction loss. SSPF is frequently regarded as the procedure of choice because it offers advantages such as incorporating fewer motion segments in the fusion, shorter operative time and fewer blood transfusions.…”
Section: Discussionmentioning
confidence: 99%